Monitoreo y control de dispositivos residenciales vía internet - Calvo-Chaves, Juan Diego (Instituto Tecnológico de Costa Rica, 2001)
Today, many products are becoming intelligent devices thanks to electronic solutions based in digital systems. Intelligent systems allow full access to all the information available from a system via a constant communication with it. Within these parameters, surges the possibility of developing solutions that let end users access and control, from any place at any time, certain important elements of their houses. For the tasks of collecting data and controlling different devices from a remote area, a house needs to be equipped with an electronic device that has to have the function of realizing such tasks. It also has to have the ability to report its condition and to take orders from remote sources. Because of this, the ideal solution for such a device has to be based in a microcontroller, which has the versatility of letting it be programmed for an specific application, has a low cost, and a real high functionality level. Today the cheapest option for remote access is through the Internet, because of this; the system has been developed towards a solution that can be controlled through the Internet by a, java applet, user interface and tools developed specifically to connect electronic devices with the Internet. Thanks to the development of this project, and through a graphic user interface based on a java applet, it is possible to monitor and control the lights, security, and air conditioning systems of a household. Non-the less, it is important to rescue the fact that the developed solution can be easily applied to other areas, such as the control of industrial or commercial systems.
Proyecto de graduación (Bachiller en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2001.
Keywords: Telecomunicaciones; Electrónica Industrial; Medidas de Seguridad; Software de Seguridad; Hardware